Shear Behavior of Wheat-Concrete Interface during Monotonic and Cyclic Loading - Changnv Zeng; Yuke Wang (Complexity)
The interface behavior between wheat and concrete plays a decisive role in the design of silo structures. In this paper, a series of strain-controlled monotonic direct shear (MDS) tests, cyclic direct shear (CDS) tests, and postcyclic direct shear (PCDS) tests were conducted to investigate the wheat-concrete interface behavior under monotonic and cyclic loading. The influence of cycle numbers, shear displacement amplitude, normal stress, and preloading consolidation was discussed in detail. In particular, the preloading consolidation simulates the partly discharging state of wheat. The values of peak stress increase with increasing displacement amplitude and cycles, and they change slightly after 10 cycles. The interface exhibits an overall contraction deformation during the MDS tests without preloading, but the contraction is suppressed by an alternating dilation during the DCS tests, and an overall small dilation occurs at small normal stress during PCDS tests. It is observed that the cyclic loading and preloading normal stresses result in an increasing peak strength, internal friction angle, and apparent cohesion, whereas a decrease in interface contraction deformation.